EFFECT OF THERAPEUTIC ULTRASOUND FOR NECK PAIN : A SYSTEMATIC REVIEW - Agus Prastyo, Wahyu; Investari Nugraheni, Artha; Azhari, Ririn; Merisa L, Bella; Putra, Yosie Yulanda; Ananda, Astrid; Syarfina, Afdila (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: The fourth most common cause of disability is neck discomfort, which affects more than 30% of people annually. The majority of acute neck pain episodes will go away with or without therapy, but about 50% of people will still have discomfort or recurrences on a regular basis. Aims : This systematic review is to review the effect of therapy with ultrasound for neck pain.Methods: This study demonstrated compliance with all requirements by means of a comparison with the standards established by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020. Thus, the specialists were able to guarantee that the research was as current as feasible. Publications released between 2014 and 2024 were considered for this search strategy. This was accomplished by utilizing a number of distinct online reference sites, including Pubmed, ScienceDirect, and SagePub. It was determined that reviews, previously published works, and partially completed works would not be included. Result: In the PubMed database, the results of our search brought up 5375 articles, whereas the results of our search on SAGEPUB brought up 7781 articles, our search on SCIENCE DIRECT brought up 30045 articles. The results of the search conducted for the last year of 2014 yielded a total 2864 articles for PubMed, 3376 articles for SAGEPUB and 13342 articles for SCIENCE DIRECT. In the end, we compiled a total of  7 papers, 5 of which came from PubMed, 1 of which came from SAGEPUB and 1 of which came from SCIENCE DIRECT. We included seven research that met the criteria.Conclusion: In summary, therapeutic ultrasonography is a safe treatment that has the potential to lessen pain intensity more than sham or no treatment at all. It is unclear if using therapeutic ultrasonography in addition to other traditional therapies reduced pain, increased disability, or improved quality of life.